3D imaging of a rice pollen grain using transmission X‐ray microscopy. (25th June 2015) - Wang, Shengxiang; Wang, Dajiang; Wu, Qiao; Gao, Kun; Wang, Zhili; Wu, Ziyu
<x xml:space="preserve">Abstract</x> For the first time, the three‐dimensional (3D) ultrastructure of an intact rice pollen cell has been obtained using a full‐field transmission hard X‐ray microscope operated in Zernike phase contrast mode. After reconstruction and segmentation from a series of projection images, complete 3D structural information of a 35 µm rice pollen grain is presented at a resolution of ∼100 nm. The reconstruction allows a clear differentiation of various subcellular structures within the rice pollen grain, including aperture, lipid body, mitochondrion, nucleus and vacuole. Furthermore, quantitative information was obtained about the distribution of cytoplasmic organelles and the volume percentage of each kind of organelle. These results demonstrate that transmission X‐ray microscopy can be quite powerful for non‐destructive investigation of 3D structures of whole eukaryotic cells.